(untitled) (Fiep Bulletin - online, 2014)
Abstract: Physical Activity and mainly the high intensity and long duration great cause stress to the human body modifying temporarily his metabolism. Some products and by-products are formed during this process where the body answers and looks its balance almost that immediately so that this exactly organism can support a load of still bigger exercise in a next event (stress). Being thus the present study has characteristics of the type comparative descriptive of field and objective compare concentrations the blood concentration of Urea. Úric Acid, Ammonia and Creatinine from practicing athletes of Triathlon. The used instrument was the Test of field race with duration of 120 minutes 75-85 % of the maximum heart hate. Had been used 7 individuals with ages between 25 and 44 years old practicing of its at least 6 years. to leave of these boarded subjects it is intended to place in question the interferences of practical activities of long duration and high intensity in the concentration of nitrogenated compound in the blood. The gotten results had been that significant differences (p<0,05) for the concentrations Urea, Úric Acid, and Creatinine in the daily pay and the one after test, the Ammonia cannot be dosed because the lack of apparatus for collection in the test place.